The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s40623-018-0864-y
|View full text |Cite
|
Sign up to set email alerts
|

Survey of conditions for artificial aurora experiments by the second electron gyro-harmonic at EISCAT Tromsø using dynasonde data

Abstract: We report a brief survey of matching conditions for artificial aurora optical experiments utilizing the second electron gyro-harmonic (2.7-MHz frequency) in F region heating with O-mode at the EISCAT Tromsø site using dynasonde data from 2000 to 2017. Our survey indicates the following: The possible conditions for successful artificial aurora experiments are concentrated on twilight hours in both evening and morning, compared with late night hours; the possible conditions appear in fall, winter, and spring, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…However, the chances of possible observations are not high and mostly hopeless during the solar minimum period. In the following report (Tsuda et al 2018b), they surveyed the possibility of artificial aurora experiment if they can use 2.7 MHz radio wave for heating. They suggested that, by decreasing the frequency of the heating radio wave from 4 to 2.7 MHz, the chance of experiment is much larger and becomes possible even during the solar minimum period.…”
Section: New Observations and Survey For New Experimentsmentioning
confidence: 99%
“…However, the chances of possible observations are not high and mostly hopeless during the solar minimum period. In the following report (Tsuda et al 2018b), they surveyed the possibility of artificial aurora experiment if they can use 2.7 MHz radio wave for heating. They suggested that, by decreasing the frequency of the heating radio wave from 4 to 2.7 MHz, the chance of experiment is much larger and becomes possible even during the solar minimum period.…”
Section: New Observations and Survey For New Experimentsmentioning
confidence: 99%